2000
DOI: 10.1182/blood.v96.4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Blood group A and B antigens are strongly expressed on platelets of some individuals

Abstract: It is widely thought that expression of ABH antigens on platelets is insufficient to materially affect the survival of ABH-incompatible platelets in transfusion recipients, but anecdotal reports of poor survival of A and B mismatched platelets suggest that this is not always the case. The A and B antigen expression on platelets of 100 group A1 and group B blood donors was measured, and 7% and 4%, respectively, had platelets whose A and B antigen levels consistently exceeded the mean plus 2 SD. On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 34 publications
9
73
3
Order By: Relevance
“…Clinically, our findings are of interest to PLT transfusion support. As observed in prior reports, group A individuals lacking the A 1 allele expressed the A antigen only weakly on PLTs. The A antigen MFI among A 2 /O , A 2 /A 2 , and A 2 B individuals (mean, 159 ± 131) was slightly greater than the background MFI seen among group O subjects (mean, 63 ± 32), providing laboratory evidence to support the use of PLTs from A 1 ‐negative donors as a substitute for group O donor PLTs during transfusion support of group O or group B recipients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Clinically, our findings are of interest to PLT transfusion support. As observed in prior reports, group A individuals lacking the A 1 allele expressed the A antigen only weakly on PLTs. The A antigen MFI among A 2 /O , A 2 /A 2 , and A 2 B individuals (mean, 159 ± 131) was slightly greater than the background MFI seen among group O subjects (mean, 63 ± 32), providing laboratory evidence to support the use of PLTs from A 1 ‐negative donors as a substitute for group O donor PLTs during transfusion support of group O or group B recipients.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with others, we found that H antigen was much more strongly expressed than A antigen on PLTs. In contrast with RBCs where H expression is inversely related to A expression, Curtis and coworkers, Cooling and coworkers, and Sant'Anna Gomes and coworkers reported that on PLTs increasing H antigen was directly related to increasing A antigen, a result we also observed among A 1 /A 1 individuals, but not among A 1 /O persons. As reported by Le Pendu and colleagues, Ogasawara and colleagues, and Cooling and colleagues, we also found that A antigen expression was not related to secretor status.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Blood types of fathers were A 1 (Sey) and A 2 B (Hug). Because high‐titer IgG maternal antibodies specific for blood groups A or B can cause neonatal thrombocytopenia in infants who possess a genetic trait that causes PLTs to express many times the normal levels of A or B antigens, 12,19 the maternal sera were absorbed with washed group A 1 and B red blood cells. This treatment had no effect on the reactions with paternal PLTs.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal samples from suspected NAIT cases were tested against paternal PLTs and PLTs from group O donors of known phenotypes using flow cytometry as previously described 10‐12 . Antibodies reactive with GPIIb/IIIa, GPIb/IX, GPIa/IIa, and GPIV were detected by direct and modified antigen‐capture enzyme‐linked immunosorbent assay (ELISA, ACE, and MACE) 10 …”
Section: Methodsmentioning
confidence: 99%